Measuring Consumer Valuation of Limited Provider Networks - Ericson, Keith Marzilli; Starc, Amanda (American Economic Review, 2015)
We measure the breadth of insurance networks in the Massachusetts health insurance exchange. Using our measures, we estimate consumer willingness-to-pay for broad and narrow networks. We find that consumers have a wide range of plans available with dramatically different networks. While consumers value broader networks, their willingness-to-pay is smaller than the brand premium, indicating an additional role for brand preferences. Consumers place additional value on star hospitals, which may affect upstream negotiations. Finally, we find significant geographic heterogeneity in the value of broad networks.